Upaya Peningkatan Kompetensi Guru dalam Pembelajaran Matematika melalui Inovasi Pemanfaatan Media Pembelajaran yang Atraktif di SD Negeri 2 Pandanrejo tahun pelajaran 2019/2020 - Yuniati, Ida (Universitas Nahdlatul Ulama Pasuruan, 2022)
This study aims to improve teacher competence in mathematics subjects with innovations using attractive learning media at SD Negeri 2 Pandanrejo for the 2019/2020 school year. This research was conducted on the basis of observations which show that the results of observations that have been made still produce very few teachers who innovate in the use of learning media. Therefore, competence must be improved through coaching activities carried out by the principal. This research uses School Action Research (PTS) with 2 cycles. Each cycle consists of stages of planning, implementing actions, observing and reflecting. The data obtained from observations and evaluations of teacher performance. The data were then analyzed usinga descriptive approach. The results of the study show that the guidance carried out by the principal in innovative use of attractive mathematics learning media can improve the competence of teachers at SD Negeri 2 Pandanrejo for the 2019/2020 school year.In the first cycle the teacher's ability reached 42% and in the second cycle the teacher's ability increased to 73%.